A solution-processable near-infrared thermally activated delayed fluorescent dye with a fused aromatic acceptor and aggregation induced emission behavior. Issue 12 (19th January 2022) - Congrave, Daniel G.; Drummond, Bluebell H.; Gu, Qinying; Montanaro, Stephanie; Francis, Haydn; Riesgo-González, Víctor; Zeng, Weixuan; Matthews, Campbell S. B.; Dowland, Simon; Wright, Iain A.; Grey, Clare P.; Friend, Richard H.; et al.
Abstract : Here a new electron donor is developed to endow a near-IR TADF molecule with good solubility for solution processing and AIE behavior. This is the first AIE TADF material with all PL > 700 nm. Abstract : The unique synergy of properties offered by an efficient and processable near-infrared thermally activated delayed fluorescent (NIR TADF) dye could be transformative across research fields. Here, a solution-processable NIR TADF material is demonstrated (CAT-TPE ). Good solubility is achieved through the use of a new tetraphenylethylene (TPE)-based triphenylamine electron donor. TADF is confirmed through variable temperature time-resolved measurements at a peak photoluminescence (PL) wavelength of 842 nm in a solution-processed film. An OLED with good roll-off characteristics for a solution-processed NIR TADF device is reported with electroluminescence λ max > 700 nm. CAT-TPE also demonstrates classic aggregation induced emission (AIE) behavior, being more emissive when aggregated than in solution with all PL > 700 nm. This work opens the door to the considerably enhanced structural diversity of solution-processable NIR TADF and will inform the design of future high efficiency AIE NIR TADF materials.